2022
DOI: 10.3389/fpsyg.2022.816864
|View full text |Cite
|
Sign up to set email alerts
|

Speech Perception in Older Adults: An Interplay of Hearing, Cognition, and Learning?

Abstract: Older adults with age-related hearing loss exhibit substantial individual differences in speech perception in adverse listening conditions. We propose that the ability to rapidly adapt to changes in the auditory environment (i.e., perceptual learning) is among the processes contributing to these individual differences, in addition to the cognitive and sensory processes that were explored in the past. Seventy older adults with age-related hearing loss participated in this study. We assessed the relative contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 127 publications
(192 reference statements)
0
2
0
Order By: Relevance
“…Inhibition, which a sub-domain of executive function ( Figure 1 ), and processing speed are also cognitive functions associated with reduced auditory performance ( 87–89 ). Different domains of cognition appear to be more strongly predictive of listening ability for more difficult listening tasks ( 90 , 91 ). A meta-analysis ( 92 ) provided an overview over various cognitive functions and their association with different SIN tasks.…”
Section: The Effects Of Cognitive Change On Speech Perceptionmentioning
confidence: 99%
“…Inhibition, which a sub-domain of executive function ( Figure 1 ), and processing speed are also cognitive functions associated with reduced auditory performance ( 87–89 ). Different domains of cognition appear to be more strongly predictive of listening ability for more difficult listening tasks ( 90 , 91 ). A meta-analysis ( 92 ) provided an overview over various cognitive functions and their association with different SIN tasks.…”
Section: The Effects Of Cognitive Change On Speech Perceptionmentioning
confidence: 99%
“…It must be noted that while these differences are statistically significant, they are modest in size and clinical impact. It is also acknowledged that speech perception is affected by other factors apart from cochlear tissue states including etiology, age, cognition and level of education, which were not controlled for in this study ( Heutink et al 2021 ; Shechter Shvartzman et al 2022 ). No significant differences were seen in the most complex auditory task of speech-in noise (SRT); the lack of difference between groups here might reflect the low ceiling limit of this test.…”
Section: Discussionmentioning
confidence: 98%
“…Value-directed strategic processing subsumes other attentional processes, including selective attention ( Anderson, 2013 ). In the context of ARHL, selective attention has been long examined ( Barr and Giambra, 1990 ; Craik, 2007 ; Shinn-Cunningham and Best, 2008 ; Van Gerven and Guerreiro, 2016 ; Dai et al, 2018 ), especially in the context of speech recognition ( Humes and Dubno, 2010 ; Nuesse et al, 2018 ; Fuglsang et al, 2020 ; Shechter Shvartzman et al, 2022 ). On various tasks, such as coordinate response measure ( Humes et al, 2006 , 2017 ), attentive matrices ( Bonmassar et al, 2022 ), n- back with distracting stimuli ( Guerreiro and Van Gerven, 2017 ), Stroop ( Guerreiro and Van Gerven, 2017 ; Gillingham et al, 2018 ; Ren et al, 2019 ; Huber et al, 2020 ; Chavant and Kapoula, 2022 ), and dichotic listening tasks ( Shinn-Cunningham and Best, 2008 ; Torrente et al, 2022 ), studies have found alterations in selective attention in older adults with ARHL relative to younger and older adults with normal hearing.…”
Section: Introductionmentioning
confidence: 99%